Transitioning to more sustainable, low-emissions agriculture in Brazil - Pinto LFG; Hajjar, Reem; Newton, Peter; Agrawal, A.; Adshead D; Bini, Denici; Bogaerts, Meghan; Cirhigiri, Lora; Maguire-Rajpaul, Victoria Alice; Gonzáles Chaves, A.; McDermott C; Milder, Jeffrey C.; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
KEY FINDINGS Cattle producers joined sustainability initiatives primarily to increase production, reduce production costs, learn new practices and access innovations, and because of their interest in sustainability. Farmers who shifted to sustainable intensification practices increased their productivity. Some also accessed new markets and a minority earned higher prices. Producers sought farming advice mostly from nearby farmers and technicians promoting sustainability initiatives. The cost of changing farm practices, insufficient technical assistance or capacity, and difficulty in complying with legal standards were the major barriers preventing other cattle producers from participating in sustainability initiatives. The greenhouse gas (GHG) emissions per kg of beef of cattle farmers in sustainable intensification programs were 18% lower compared to neighboring farms not in the programs. Early life-cycle cattle ranching (e.g. calving, early rearing), commonly associated with deforestation, has been more engaged with NGO initiatives providing support and agronomic outreach rather than formal standards and reporting.